The Unchanging Pattern of Pulmonary Tuberculosis - Grzybowski, Stefan (1963)
Study of mortality from pulmonary tuberculosis in Ontario between 1881 and 1961 reveals a steady decline in rates since the beginning of this century, affecting both sexes and all age groups. This decline has been much faster in the younger than in the older age groups. When the mortality rates are studied for groups of men and women born within 10-year periods (10-year cohorts) an orderly pattern of mortality emerges, consisting of two distinct phenomena. First, the shape of the “cohort” curves is always similar: the mortality rates rise sharply in childhood and the peak is reached in early adult life, followed by a gradual descent. This appears to be a basic but unexplained feature of pulmonary tuberculosis. Secondly, each cohort shows through its life span a lower mortality rate than the previous cohort, but a higher rate than the succeeding one; it is suggested that this is primarily due to a decline in intensity of tuberculous infection over the past several decades. The high tuberculosis rates seen now in the elderly are but the residue of the much higher rates experienced by these people early in their lives.